The experimental study on integrated hydraulic fracturing of coal measures gas reservoirs. (15th June 2020) - Su, Xianbo; Li, Feng; Su, Linan; Wang, Qian
Highlights: Integrated stimulation is a difficult project in coal measures gas reservoirs. The formation permeability and breakdown pressure are main influencing factors. Flow rate injection and temporary ball blocking are effective methods for fracturing. Interlayer crossflow is conductive to balance the factureing process. Abstract: Coal measures are rich in coalbed methane, shale gas and tight sandstone gas, and the three gases co-exploration has become a potentially promising technology in China. During the process of integrated hydraulic fracturing of three gas formations in coal measures, interlayer contradiction occurs due to the formation heterogeneity, which is the key to restricting the application of this technology. In this paper, an experimental device has been designed to study the influencing factors for integrated hydraulic fracturing in coal measure gas reservoir. The results of experimental test and theoretical analysis indicate that the formation permeability and breakdown pressure are the main factors affecting hydraulic fracturing process, and the formations with large difference in these two factors always induce an uneven distribution of fracturing fluid and poor effect of integrated hydraulic fracturing. High flow rate pumping injection rate is conducive to the even distribution of fracturing fluid in various formations. Meanwhile, the proper ball injection is used to limit fluid flowrate to ensure the fluid pressure in high permeability formation is higher than it in low permeability formation, fracturing fluid can flow to low permeability formation through perforation hole. In addition, interlayer crossflow occurs during the migration of fracturing fluid and causes fluid flow to low permeability formation, which is also conducive to the even fracturing. Therefore, high flow rate pumping injection, ball injection and interlayer crossflow control are effective measures for achieving the integrated hydraulic fracturing of coal measure gas reservoirs.